SYNTHESIS OF SOME 7-AZAINDOLE DERIVATIVES: THEIR CYTOTOXICITY AND ANTIBACTERIAL ACTIVITY (Biological Sciences - PJSIR, 2022)
In thecourseofpharmaco-chemical studies, a number of new 7-azaindolederivatives have been prepared.The spectroscopictechniques such as IH NMR, ElMS, UV and IR were utilized for their structure elucidation. These compoundswere tested against a variety of Gram + ve and Gram-ve bacteria. These compounds were also screened for their cytotoxicityagainst Artemia salina. Compound IV displayed significant antibacterial activity amongst all the testedcompounds. Whereas compound VI was found to be the most significant cytotoxic when screened through brine shrimpbioassay.